Los memorialistas de la bohemia (1903-1924) (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2024)
There are very few memoirs of those who have been considered components of bohemian life in Spain. The aim of this article is to give an overview of how they have integrated this world into their personal memories and, also, to glean their motivations and points in common, which denote a coincidence in the taste for transgression as a reflection of Modernism. Zamacois, Bonafoux, Dicenta and Gómez Carrillo, three of them born in Spanish America, were the pioneers whose memoirs are here reviewed following the order of their appearance so to highlight some details about their relationship with the bohemian cohort. We also offer a less in-depth chronological analysis of the memoirs and diaries of other authors such as Ortiz de Pinedo, Buscarini, Blanco-Fombona, Gómez de la Serna and Noel.
Keywords: Spanish Bohemia; Memoirs; Tremendism; Transgression